PENGARUH MOTIVASI BELAJAR DAN PEMANFAATAN SARANA BELAJAR TERHADAP HASIL BELAJAR IPS TERPADU - Agtifah Sari; Raden Gunawan Sudarmanto; Yon Rizal (FKIP Unila, 2014)
The aim of this research is to know the influence of learning motivation and the utilization of facility in school on learning outcomes for Integrated Social Science. The population were 343 students and the sample obtained 185 students. Looking for the sample was using Slovin formula. The method in this research is descriptive verification with ex post facto and surveys approach. The sampling technique is probability sample by using simple random sampling. The first and second hypothesis was testing by using simple linear regression. The third hypothesis is using multiple linear regression. The analysis indicated that: (1) there is an effect of learning motivation toward learning outcomes for Integrated Social Science, (2) there is an effect of the utilization of facility in school toward learning outcomes for Integrated Social Science, (3) there is an effect of learning motivation and utilization of facility in school toward learning outcomes for Integrated Social Science. Penelitian ini bertujuan untuk mengetahui pengaruh motivasi belajar dan pemanfaatan sarana belajar di sekolah terhadap hasil belajar IPS Terpadu. Populasi penelitian sebanya 343 siswa dan sampel diperoleh 185 siswa. Pencarian sampel menggunakan rumus slovin. Metode penelitian deskriptif verifikatif dengan pendekatan ex post facto dan survey. Teknik pengambilan sampel adalah probability sample dengan menggunakan simple random sampling. Pengujian hipotesis pertama dan kedua menggunakan regresi linier sederhana. Pengujian hipotesis ketiga menggunakan regresi linier multiple. Berdasarkan analisis data dinyatakan bahwa: (1) ada pengaruh motivasi belajar terhadap hasil belajar IPS Terpadu, (2) ada pengaruh pemanfaatan sarana belajar terhadap hasil belajar IPS Terpadu, (3) ada pengaruh motivasi belajar dan pemanfaatan sarana belajar di sekolah terhadap hasil belajar IPS Terpadu. Kata kunci: hasil belajar, motivasi belajar, pemanfaatan sarana belajar.